2015
DOI: 10.1016/j.nuclphysb.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

ODE/IM correspondence and Bethe ansatz for affine Toda field equations

Abstract: We study the linear problem associated with modified affine Toda field equation for the Langlands dual $\hat{\mathfrak{g}}^\vee$, where $\hat{\mathfrak{g}}$ is an untwisted affine Lie algebra. The connection coefficients for the asymptotic solutions of the linear problem are found to correspond to the $Q$-functions for $\mathfrak{g}$-type quantum integrable models. The $\psi$-system for the solutions associated with the fundamental representations of $\mathfrak{g}$ leads to Bethe ansatz equations associated wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Recall that in Corollary 4.5 we applied the tensor product of Lie algebra homomorphisms ⊗ ⊗ π to the Poisson brackets of formal fields from Proposition 4.4 to obtain the Poisson brackets of the g-valued classical fields (53). In this section we similarly apply the linear map ⊗ ⊗ π ⊗ id to the algebra of Lax matrices (63) from Proposition 4.7.…”
Section: Twist Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recall that in Corollary 4.5 we applied the tensor product of Lie algebra homomorphisms ⊗ ⊗ π to the Poisson brackets of formal fields from Proposition 4.4 to obtain the Poisson brackets of the g-valued classical fields (53). In this section we similarly apply the linear map ⊗ ⊗ π ⊗ id to the algebra of Lax matrices (63) from Proposition 4.7.…”
Section: Twist Functionmentioning
confidence: 99%
“…Specifically, they showed that the functional relations and analytic properties characterising the vacuum eigenvalues of the Q-operators of quantum sine/sinh-Gordon theory were the same as those satisfied by certain connection coefficients of the auxiliary linear problem of the classical modified sinh-Gordon equation for a suitably chosen classical solution. Subsequently, various higher rank generalisations of this massive ODE/IM correspondence for quantum affine g-Toda field theories were also conjectured, when g is of type A for rank 3 in [24] and for general rank n in [1], and more recently for a general untwisted affine Kac-Moody algebra g in [52,53] as well as examples of twisted type in [54]. Another important quantum integrable field theory for which a massive ODE/IM correspondence has been conjectured in [63], and further studied in [7,6], is the Fateev model [35].…”
Section: Motivation and Introductionmentioning
confidence: 99%
“…These results were extended to massive Integrable Quantum Field Theories (IQFT) [27] (for recent developments, see also refs. [28][29][30][31][32][33][34][35]). The general relation of this type will be referred to in the paper as the ODE/IQFT correspondence.…”
Section: Jhep01(2018)021mentioning
confidence: 99%
“…For a classical Lie algebra g the ODEs have been constructed by [19,27,22]. Let us consider the linear problem for the modified affine Toda field equation forĝ of a simply laced Lie algebra g of rank n. In the conformal limit [20,22,24], it takes the form:…”
Section: Quantum Spectral Curves For D N and E N Casesmentioning
confidence: 99%
“…The ordinary differential equations for the integrable models associated with the Bethe equations of a classical Lie algebra g have been proposed in [19]. For a general Lie algebra g, it is obtained from the conformal limit of the linear problem for the modified affine Toda field equations associated withĝ ∨ , while the full linear problem describes the massive version of the ODE/IM correspondence [20,21,22,23,24,25,26] (see also [27] for a classical Lie algebra case). Hereĝ denotes the untwisted affine Lie algebra of g andĝ ∨ the Langlands dual ofĝ.…”
Section: Introductionmentioning
confidence: 99%